Economic Effects of Taxing Different Organizational Forms under a Dual Income Tax - Tobias Lindhe; Jan Södersten; Ann Öberg (Uppsala University, Department of Economics, 2003)
This paper analyzes the economic effects of different income splitting rules for closely held corporations and sole proprietorships/partnerships in a tax system with a dual income tax. We conclude that the tax rules for closed corporations offer roughly the same cost of capital as for widely held corporations. Compared to corporate firms, the cost of capital is lower for sole proprietorships/partnerships, because the income-splitting rules both neutralize the impact of the high labor income tax and avoid the two-tier taxation on the corporate form of organization. Adding risk to the model shows that closely held corporations have a lower cost of capital than would be the case without income-splitting rules.
urn:nbn:se:uu:diva-4487
Keywords: H24; H25; H32; 330; Dual income taxation; small business taxation; tax avoidance; income splitting; cost of capital; Duale Einkommensteuer; Lohnsteuer; Kapitalertragsteuer; Kapitalkosten; Theorie; Schweden; Norwegen; Finnland